2012
DOI: 10.1111/j.1444-0938.2012.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Macular thickness as determined by optical coherence tomography in relation to degree of myopia, axial length and vitreous chamber depth in Malay subjects

Abstract: Purpose: This study aimed to determine the relationship between macular thickness and spherical equivalent refraction (SER), axial length (AL) and vitreous chamber depth (VCD) in Malay subjects. Methods: Sixty-three subjects (aged 19-24 years) with a mean SER of -1.79 Ϯ 2.24 D, mean axial length of 24.26 Ϯ 1.35 mm and mean vitreous chamber depth of 17.02 Ϯ 1.33 mm were included in this clinical cross-sectional study. Stratus optical coherence tomography (Time Domain optical coherence tomography) was used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…This suggests the influence of axial length over macular thickness in myopia. This correlates with the study done by Lam et al, in which minimum foveal thickness increased with axial length [14][15][16][17][18][19]. Similarly, Hwang et al, [20] also found that in healthy young myopic eyes showed thinner macular thickness, lower macular volume and thicker foveal thickness were associated with longer axial length.…”
Section: Discusionsupporting
confidence: 85%
See 1 more Smart Citation
“…This suggests the influence of axial length over macular thickness in myopia. This correlates with the study done by Lam et al, in which minimum foveal thickness increased with axial length [14][15][16][17][18][19]. Similarly, Hwang et al, [20] also found that in healthy young myopic eyes showed thinner macular thickness, lower macular volume and thicker foveal thickness were associated with longer axial length.…”
Section: Discusionsupporting
confidence: 85%
“…This suggests that the axial length increases with increasing degree of myopia. The degree of myopia and elongation of globe are associated with thinning of most areas of perifovea was found in a study by oathman SF et al, [18].…”
Section: Discusionmentioning
confidence: 84%
“…23,28,29 While there was significant correlation between foveal thickness and both SER and AL in the Pearson correlation analysis, there was no significant correlation in the partial correlation analysis. A number of studies have reported significant correlation between macular thickness and SER or AL, 6,7,9,22,23,25 but the analyses were not controlled for other possible confounding variables. Our study showed that after adjustment for the other factors, the association between macular thickness and SER or AL was insignificant.…”
Section: Discussionmentioning
confidence: 98%
“…4 Therefore, the assessment of macular parameters such as macular thickness and macular volume in myopic children is of significance when evaluating ocular conditions that are likely to induce macular thickening or thinning. [5][6][7] A number of studies have reported the correlation between macular thickness and refractive error or axial length (AL) using a noninvasive method, optical coherence tomography (OCT). 6,7 However, the conclusions were partly inconsistent in terms of regional and racial variations.…”
mentioning
confidence: 99%
See 1 more Smart Citation